Antibiofilm activity of tert-BuOH functionalized ionic liquids with methylsulfonate counteranions - Navale, Govinda R.; Dharne, Mahesh S.; Shinde, Sandip S. (RSC Advances, 2015)
A series of varying alkyl chain length substituted tert-BuOH-functionalized-imidazolium mesylate salts [alkyl-(t)OHim][OMs] were synthesized and evaluated for antimicrobial activity and antibiofilm potential on selected pathogenic microorganisms including bacteria (Gram positive and Gram negative), yeast, and fungi. The dodecyl substituted ionic liquid [C-12-(t)OHim][OMs] significantly prevented the biofilm formation of S. epidermidis at 100 mu M concentration as well as showed noteworthy antimicrobial activity. We conclude that the ionic liquids (ILs) bearing chain lengths lower than the dodecyl length were found to be less effective against most of the tested pathogenic microorganisms.

Oxidative and membrane stress-mediated antibacterial activity of WS2 and rGO-WS2 nanosheets - Navale, Govinda R.; Rout, Chandra Sekhar; Gohil, Kushal N.; Dharne, Mahesh S.; Late, Dattatray J.; Shinde, Sandip S. (RSC Advances, 2015)
Graphene-based materials have strong cytotoxic attributes against bacteria due to their unique physicochemical properties. We examined the antibacterial activities of nanosheets of the graphene analogue tungsten disulphide (WS2) and a composite of reduced graphene oxide-tungsten disulphide (rGO-WS2), comparing them with reduced graphene oxide (rGO) by a time and concentration dependent viability assay and growth curve studies against four bacterial strains: Gram negative Escherichia coli (E. coli) and Salmonella typhimurium (S. typhimurium), and Gram positive Bacillus subtilis (B. subtilis) and Staphylococcus epidermidis (S. epidermidis). The nanosheets of the rGO-WS2 composite caused a more significant retardation in bacterial growth and inhibitory effect on the tested bacterial strains than WS2, followed by rGO. The tested E. coli and B. subtilis strains were more susceptible than the other strains. A mechanistic study revealed that rGO and WS2 did not produce the superoxide anion (O-2(-)) or reactive oxygen species (ROS), but the nanocomposite of rGO-WS2 did produce both. However, all these materials did oxidize glutathione, which serves as a redox state mediator in bacteria. We conclude that the antimicrobial mechanism is due to the combined effect of initial cell deposition on the rGO-WS2 materials, the membrane stress due to direct contact with the nanosheets, and the produced superoxide anion-independent oxidation mechanisms. The beneficial aspects of the physicochemical properties of rGO-WS2, such as its size and conductivity, can be precisely customized to reduce its health and environmental risk factors.

Stereoselective quenching of cedryl carbocation in epicedrol biosynthesis - Shinde, Sandip S.; Navale, Govinda R.; Said, Madhukar S.; Thulasiram, Hirekodathakallu V. (Tetrahedron Letters, 2016)
Epicedrol synthase catalyzes the cyclization of achiral diphosphate substrate, (E,E)-farnesyldiphosphate (FPP) into epicedrol. GC-MS analysis of assay extracts obtained by incubating FPP with epicedrol synthase in 21.6 at % H2(18)O buffer showed the molecular ion of 224 for epicedrol. The labeled oxygen study presented here unambiguously demonstrates that the hydroxyl group of the epicedrol synthase enzymatic product, epicedrol, is derived from a water molecule, not from the phosphate moiety of the FPP. (C) 2016 Elsevier Ltd. All rights reserved.

Synthesis, biological evaluation and molecular docking of novel coumarin incorporated triazoles as antitubercular, antioxidant and antimicrobial agents - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Shingate, Bapurao B.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Khedkar, Vijay M.; Nawale, Laxman; Sarkar, Dhiman; Navale, Govinda R.; Shinde, Sandip S. (Medicinal Chemistry Research, 2016)
A series of new coumarin-based 1,2,3-triazole derivatives were designed, synthesized and evaluated for their antitubercular activity in vitro against Mycobacterium tuberculosis H37Ra, antioxidant activity by DPPH radical scavenging assay, antimicrobial activity in vitro against three gram-positive bacteria (Staphylococcus aureus, Micrococcus luteus and Bacillus cereus) and three gram-negative bacteria (Escherichia coli, Pseudomonas fluorescens and Flavobacterium devorans as well as three fungi (Aspergillus niger, Penicillium chrysogenum and Curvularia lunata). The bioactive assay showed that some synthesized coumarin triazoles displayed comparable or even better antitubercular, antioxidant, antibacterial and antifungal efficacy in comparison with reference drugs. Furthermore, docking study has been performed against DprE1 enzyme of M. tuberculosis that showed good binding interactions. Moreover, the synthesized compounds were also analyzed for ADME properties and showed potential to build up as good oral drug candidates. New coumarin-based 1,2,3-triazole derivatives were designed, synthesized and evaluated for their antitubercular, antioxidant, antibacterial and antifungal activity. Some of the coumarin-based triazole derivatives displayed comparable or even better efficacy in comparison with reference drugs. Molecular docking study has been performed against DprE1 enzyme of Mycobacterium tuberculosis showed good binding interactions. [GRAPHICS] .
Keywords: 1; 2; 3-Triazole; ADME prediction; Antimicrobial; Antioxidant; Antitubercular; Click chemistry; Docking study

Synthesis of deuterated isopentyl pyrophosphates for chemo-enzymatic labelling methods: GC-EI-MS based 1,2-hydride shift in epicedrol biosynthesis - Said, Madhukar S.; Navale, Govinda R.; Gajbhiye, Jayant M.; Shinde, Sandip S. (RSC Advances, 2019)
A sesquiterpene epicedrol cyclase mechanism was elucidated based on the gas chromatography coupled to electron impact mass spectrometry fragmentation data of deuterated (H-2) epicedrol analogues. The chemo-enzymatic method was applied for the specific synthesis of 8-position labelled farnesyl pyrophosphate and epicedrol. EI-MS fragmentation ions compared with non-labelled and isotopic mass shift fragments suggest that the H-2 of C6 migrates to the C7 position during the cyclization mechanism.

Biosensors: frontiers in rapid detection of COVID-19 - Samson, Rachel; Navale, Govinda R.; Dharne, Mahesh S. (3 Biotech, 2020)
The rapid community-spread of novel human coronavirus 2019 (nCOVID19 or SARS-Cov2) and morbidity statistics has put forth an unprecedented urge for rapid diagnostics for quick and sensitive detection followed by contact tracing and containment strategies, especially when no vaccine or therapeutics are known. Currently, quantitative real-time polymerase chain reaction (qRT-PCR) is being used widely to detect COVID-19 from various types of biological specimens, which is time-consuming, labor-intensive and may not be rapidly deployable in remote or resource-limited settings. This might lead to hindrance in acquiring realistic data of infectivity and community spread of SARS-CoV-2 in the population. This review summarizes the existing status of current diagnostic methods, their possible limitations, and the advantages of biosensor-based diagnostics over the conventional ones for the detection of SARS-Cov-2. Novel biosensors used to detect RNA-viruses include CRISPR-Cas9 based paper strip, nucleic-acid based, aptamer-based, antigen-Au/Ag nanoparticles-based electrochemical biosensor, optical biosensor, and Surface Plasmon Resonance. These could be effective tools for rapid, authentic, portable, and more promising diagnosis in the current pandemic that has affected the world economies and humanity. Present challenges and future perspectives of developing robust biosensors devices for rapid, scalable, and sensitive detection and management of COVID-19 are presented in light of the test-test-test theme of the World Health Organization (WHO).
Keywords: Biosensors; COVID-19; Rapid detection; SARS-CoV-2

Continuous interfacial centrifugal separation and recovery of silver nanoparticles - Deshpande, Jaydeep B.; Navale, Govinda R.; Dharne, Mahesh S.; Kulkarni, Amol A. (Chemical Engineering & Technology, 2020)
Continuous-flow separation and recovery of silver nanoparticles (AgNPs) using an annular centrifugal extractor (ACE) is demonstrated. Separation was achieved at the liquid-liquid interface based on the balance between centrifugal force and the solubility of the capping agent. A mathematical model is presented to understand the mechanism in greater detail. The separation of poly(vinylpyrrolidone) (PVP)-coated AgNPs in an ACE using a strong immiscible solvent was performed. The material accumulated at the interface was separated periodically without discontinuing the operation. The method is also suitable for separation of large particles or 1D/2D nanostructures even employing a single annular centrifugal extractor. Stable AgNPs were selected for a detailed antimicrobial activity study.
Keywords: Annular centrifugal extractor; Antimicrobial activity; Continuous-flow separation; Liquid-liquid interface; silver nanoparticles

Effect of tert-alcohol functional imidazolium salts on oligomerization and fibrillization of amyloid beta (1-42) peptide - Said, Madhukar S.; Navale, Govinda R.; Yadav, Ashok; Khonde, Nilesh; Shinde, Sandip S.; Jha, Anjali (Biophysical Chemistry, 2020)
Imidazolium based IL's has gained vast interest in developing biological applications. Oligomerization and fibrillization of amyloid beta (1-42) peptide are mainly responsible for the extra-neuronal deposition of amyloid fibrils in neurodegenerative disorders like Alzheimer's disease (AD). Here, we report an effect of tert-BuOH-functional imidazolium ILs on oligomerization and fibrillization of amyloid beta (1-42) Peptide in vitro. In this study, a series of these [alkyl-(t)OHim][OMs] ILs with methyl sulphonate counter anion by varying alkyl chains were used. Among the seven protic ILs, four showed strong binding and inhibition activity for the formation of amyloid beta (1-42) aggregation by using Thioflavin T fluorescence binding assay. The secondary structural analysis of the peptide, pre-incubated with active ILs shows the loss of ordered beta-sheet amyloid structure. The longer alkyl chain ILs showed that an increased in amyloid binding and hence an inhibition effect on amyloid aggregation was enhanced. Thus, we propose that ILs could be presented as potential candidates for therapeutic intervention against Alzheimer's disease (AD).
Keywords: Aggregation; Amyloid beta (1-42) peptide; Biofilm inhibitor; Imidazolium ionic liquid

Inhibition of quorum sensing, motility and biofilm formation ofpseudomonas aeruginosaby copper oxide nanostructures - Desai, Dnyanada G.; Swarali, H.; Navale, Govinda R.; Prabhune, A.; Late, Dattatray J.; Dharne, Mahesh S.; Walke, Pravin S. (Journal of Cluster Science, 2020)
Quorum sensing (QS) is the communication between bacterial cells governed by their population density and regulated by the genes controlling virulence factors and biofilm formation. Multiple mechanisms of biofilms are resistive to antimicrobial chemotherapy; therefore novel strategies are required to overcome its limitations. Here, we report the effect of various copper oxide nanostructures (CuO-NSs) on quorum sensing inhibition. The two-dimensional CuO-NSs such as interlaced nanodiscs, nanodiscs and leaf-shaped nanosheets are prepared via a simple chemical method. The Quorum sensing inhibition (QSI) activity of all the CuO-NS are examined using reporter strainChromobacterium violaceumCV026 andEscherichia colipSB1142. We found that the CuO-interlaced nanodisc structures exhibit better QSI activity than nanodiscs and leaf-shaped sheets. The interlaced nanodisc structures are inhibited various long-chainN-acyl homoserine lactones (AHLs) mediated QS individually and confirmed by other QS-associated phenomena forPseudomonas aeruginosa, including biofilm inhibition, inhibition of virulence factors such as pyocyanin, protease production and swarming motility. Thus QSI activity of CuO-NSs is solely dependent on specific shape offering large surface area and more active sites. The CuO-NS is effective quorum sensing inhibitors, which has potential clinical applications in the management ofP. aeruginosaassociated infections.
Keywords: aeruginosa; Biofilm; Nanostructures; P; quorum sensing; Virulence factors

Synthesis of deuterated isopentyl pyrophosphates for chemo-enzymatic labelling methods: GC-EI-MS based 1,2-hydride shift in epicedrol biosynthesis (Retraction of Vol 9, Pg 28258, 2019) - Said, Madhukar S.; Navale, Govinda R.; Gajbhiye, Jayant M.; Shinde, Sandip S. (RSC Advances, 2020)
Retraction of `Synthesis of deuterated isopentyl pyrophosphates for chemo-enzymatic labelling methods: GC-EI-MS based 1,2-hydride shift in epicedrol biosynthesis' by Madhukar S. Said et al., RSC Adv., 2019, 9, 28258-28261.

Metabolic engineering and synthetic biology for isoprenoid production in Escherichia coli and Saccharomyces cerevisiae - Navale, Govinda R.; Dharne, Mahesh S.; Shinde, Sandip S. (Applied Microbiology and Biotechnology, 2021)
Isoprenoids, often called terpenoids, are the most abundant and highly diverse family of natural organic compounds. In plants, they play a distinct role in the form of photosynthetic pigments, hormones, electron carrier, structural components of membrane, and defence. Many isoprenoids have useful applications in the pharmaceutical, nutraceutical, and chemical industries. They are synthesized by various isoprenoid synthase enzymes by several consecutive steps. Recent advancement in metabolic engineering and synthetic biology has enabled the production of these isoprenoids in the heterologous host systems like Escherichia coli and Saccharomyces cerevisiae. Both heterologous systems have been engineered for large-scale production of value-added isoprenoids. This review article will provide the detailed description of various approaches used for engineering of methyl-d-erythritol-4-phosphate (MEP) and mevalonate (MVA) pathway for synthesizing isoprene units (C-5) and ultimate production of diverse isoprenoids. The review particularly highlighted the efforts taken for the production of C-5-C-20 isoprenoids by metabolic engineering techniques in E. coli and S. cerevisiae over a decade. The challenges and strategies are also discussed in detail for scale-up and engineering of isoprenoids in the heterologous host systems.
Keywords: Escherichia coli; Isoprenoids; Metabolic engineering; Saccharomyces cerevisiae; synthetic biology

Design and synthesis of piano-stool ruthenium(II) complexes and their studies on the inhibition of amyloid ? (1-42) peptide aggregation - Singh, Sain; Navale, Govinda R.; Agrawal, Sonia; Singh, Haobam Kisan; Singla, Labhini; Sarkar, Dhiman; Sarma, Manabendra; Choudhury, Anghuman Roy; Ghosh, Kaushik (International Journal of Biological Macromolecules, 2023)
Misfolding , protein aggregation have been linked to numerous human neurodegenerative disorders such as Alzheimer's, prion , Parkinson's diseases. Ruthenium (Ru) complexes have received considerable attention in studying protein aggregation due to their interesting photophysical and photo properties. In this study, we have synthesized the novel Ru complexes ([Ru(p-cymene)Cl(L-1)][PF6](Ru-1), and [Ru(p-cymene)Cl(L-2)][PF6](Ru-2)) and investigated their inhibitory activity against the bovine serum albumin (BSA) aggregation and the A beta 1-42 peptides amyloid formation. Several spectroscopic methods were used to characterize these complexes, and the molecular structure of the complex was determined by X-ray crystallography. Amyloid aggregation and inhi-bition activities were examined using the Thioflavin-T (ThT) assay, and the secondary structures of the protein were analyzed by circular dichroism (CD) spectroscopy and transmission electron microscopy (TEM). The cell viability assay was carried out on the neuroblastoma cell line, revealing that the complex Ru-2 showed better protective effects against A beta 1-42 peptide toxicity on neuro-2a cells than the complex Ru-1. Molecular docking studies elucidate the binding sites and interactions between the Ru-complexes and A beta 1-42 peptides. The exper-imental studies revealed that these complexes significantly inhibited the BSA aggregation and A beta 1-42 amyloid fibril formation at 1:3 and 1:1 molar concentrations, respectively. Antioxidant assays demonstrated that these complexes act as antioxidants, protecting from amyloid-induced oxidative stress. Molecular docking studies with the monomeric A beta 1-42 (PDB: 1IYT) show hydrophobic interaction, and both complexes bind preferably in the central region of the peptide and coordinate with two binding sites of the peptide. Hence, we suggest that the Ru-based complexes could be applied as a potential agent in metallopharmaceutical research against Alzheimer's disease.
Keywords: Aggregation; Amyloid ?(1-42) peptide; DFT computation; Fibrillization; Molecular docking; Ruthenium complexes

Inhibition of amyloid β1-42 peptide aggregation by newly designed cyclometallated palladium complexes - Saini, Rahul; Navale, Govinda R.; Singh, Sain; Singh, Haobam Kisan; Chauhan, Rahul; Agrawal, Sonia; Sarkar, Dhiman; Sarma, Manabendra; Ghosh, Kaushik (International Journal of Biological Macromolecules, 2023)
Uncontrolled amyloid aggregation is a frequent cause of neurodegenerative disorders such as prions and Alzheimer's disease (AD). As a result, many drug development approaches focus on evaluating novel molecules that can alter self-recognition pathways. Herein, we designed and synthesized the cyclometallated pyrene (Pd-1 and Pd-3) and anthracene (Pd-2) based palladium complexes ([Pd((L-1)Cl] Pd-1, [Pd(L-2)Cl](Pd-2), and [Pd(L-3)Cl] (Pd-3)). This study explores the effect of these complexes on the aggregation, fibrillation, and amyloid formation of bovine serum albumin (BSA) and A beta(1-42) peptide. Several spectroscopic methods were used to characterize all the Pd-complexes, and the molecular structure of Pd -3 was determined by X-ray crystallography. The secondary structures were studied using circular dichroism (CD) and transmission electron microscopy (TEM), while am-yloid aggregation and inhibitory activities were investigated using the Thioflavin-T (ThT) fluorescence assay. Molecular docking of the Pd-complex (Pd-3) was done using fibril (PDB: 2BEG) and monomeric (PDB: 1IYT) peptides using Auto-dock Vina. As a result, the hydrogen bonding and hydrophobic interaction between the aromatic rings of the Pd-complexes and the amino acids of amyloid-beta peptides significantly reduced the pro-duction of ordered beta-sheets of amyloid fibrils and protein aggregation in the presence of Pd-2 and Pd-3 complexes.
Keywords: A beta(1-42) peptide; Aggregation and molecular docking; Palladium complex

Poly-gamma-glutamic acid biopolymer: a sleeping giant with diverse applications and unique opportunities for commercialization - Nair, Pranav; Navale, Govinda R.; Dharne, Mahesh S. (Biomass Conversion and Biorefinery, 2023)
Poly-gamma-glutamic acid (gamma-PGA) is a biodegradable, non-toxic, ecofriendly, and non-immunogenic biopolymer. Its phenomenal properties have gained immense attention in the field of regenerative medicine, the food industry, wastewater treatment, and even in 3D printing bio-ink. The gamma-PGA has the potential to replace synthetic non-degradable counterparts, but the main obstacle is the high production cost and lower productivity. Extensive research has been carried out to reduce the production cost by using different waste; however, it is unable to match the commercialization needs. This review focuses on the biosynthetic mechanism of gamma-PGA, its production using the synthetic medium as well as different wastes by L-glutamic acid-dependent and independent microbial strains. Furthermore, various metabolic engineering strategies and the recovery processes for gamma-PGA and their possible applications are discussed. Finally, highlights on the challenges and unique approaches to reduce the production cost and to increase the productivity for commercialization of gamma-PGA are also summarized.
Keywords: Commercialization; Multi-nutritious; Poly-gamma-glutamic acid; Waste valorization

Size does matter: antibacterial activities and cytotoxic evaluation of polymorphic CuO nanostructures - Desai, Dnyanada G.; Navale, Govinda R.; Late, Dattatray J.; Dharne, Mahesh S.; Walke, Pravin S. (Journal of Materials Science, 2023)
Nanostructured materials play a significant role in antibacterial activities. However, understanding the geometrical influence at the nanoscale in terms of size- and shape-correlated physical properties on antibacterial activities is very essential. Herein, we report the antibacterial influence of various copper oxide nanostructures (CuO NS) such as nanoparticles (NPs) (< 10 nm), nanospheres (NSs) (50-100 nm), and porous nanoflowers (NFs) (asymptotic to 350 nm). The XRD confirmed the crystalline nature of CuO NPs without impurities. The antibacterial activities of CuO NPs were investigated by the microplate dilution method and confocal laser scanning microscopic (CLSM) imaging. NPs having a diameter less than 10 nm exhibited significant damage to the bacterial cell membrane than NSs and NFs. Interestingly, NPs illustrated relatively low antibacterial activity against Gram-negative bacteria (Pseudomonas aeruginosa and Acinetobacter baumannii) than Gram-positive bacteria (Staphylococcus aureus and Staphylococcus epidermidis). Acinetobacter baumannii was found to be more susceptible to the NPs than other bacterial strains, attributed to its increased membrane permeability. The death phase was observed at a concentration of 15.6 mu g mL(-1) and 3.9 mu g mL(-1) for P. aeruginosa and A. baumannii, respectively, when treated with CuO NP after the 8 h of incubation. Similarly, for S. aureus and S. epidermidis, the death phase was observed at the concentration of 31.2 mu g mL(-1) and 250 mu g mL(-1), respectively. Furthermore, as the cell cytotoxicity measurements against human fibroblast L9239 cells revealed that CuO NPs were safe. The morphological and cell viability assay demonstrated 100% cell survival, when treated with NPs and NSs (5, 10, and 25 mu g mL(-1)), signifies no cytotoxicity. Therefore, CuO nanoparticles can be used for clinical and therapeutic applications.